2018
DOI: 10.1016/j.intfin.2018.02.004
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the US stock market reactions to energy price shocks

Abstract: This paper investigates the relationship between S&P 500 prices, viewed as a US economic barometer, and a set of energy prices, including WTI, gasoline, heating, diesel and natural gas prices, using the Quantile Autoregressive Distributed Lags (QARDL) model recently developed by Cho et al. (2015). The empirical results show a negative long-and shortrun relationship between WTI crude oil and Henry Hub natural gas prices on the one side and S&P 500 stock prices on the other side, only for medium and high quantil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(32 citation statements)
references
References 59 publications
0
32
0
Order By: Relevance
“…Since the seminal work by Draper [7], abundant papers have explored how announcements or major events are impounded into financial asset prices [8][9][10][11][12]. However, little literature deals with the price reactions to the different types of OPEC's announcements based on the event study methodology.…”
Section: Opecmentioning
confidence: 99%
“…Since the seminal work by Draper [7], abundant papers have explored how announcements or major events are impounded into financial asset prices [8][9][10][11][12]. However, little literature deals with the price reactions to the different types of OPEC's announcements based on the event study methodology.…”
Section: Opecmentioning
confidence: 99%
“…A ij . Many researchers [1,10,26,30,36,39,40,59,60,64] use the autoregressive-distributed lag model (ARDL) and the bounds testing methodology because these models can be used with a mixture of I(0) and I(1) data. In our study, we have both stationary and non-stationary variables so this approach will help in our research.…”
Section: Econometric Methodsmentioning
confidence: 99%
“…Singh [60] provided evidence that capital investment and foreign direct investment (FDI) promote economic growth in India for the period of 1970 to 2012 through an ARDL cointegration approach, whereas Paramati et al [61] documented that output, FDI inflows, and stock markets positively influence clean energy consumption. Benkraiem, Lahiani, Miloudi, and Shahbaz [30] used the quantile autoregressive distributed lags (QARDL) model and found that the medium quantiles are negative and there is a significant short-term connection between WTI crude oil and S&P 500 stock prices, as well as between Henry Hub natural gas prices and S&P 500 stock prices. For the case of Turkey, Tursoy and Faisal [41] concluded that gold prices cause stock prices in short-term, long-term, and joint forms, and crude oil also positively influences stock prices, but no proof of causality between stock prices and crude oil was found.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Overtime, the major interest in this study has basically been on global and national scales respectively. While studies like Jones and Kaul (1996), Lean and Badeeb 2017, Bastianin et al (2017), Broadstock and Filis (2014), Dutta (2017), Ftiti (2015), Gupta (2016, Kayalar et al (2017), Sharmar (2017), , Silvapulle et al 2017and Khalifa (2017) analyse either on a panel or country by country basis, studies like Cong et al (2008), Fowowe (2013), Benkraiem et al (2018), Zheng and Su (2017), Bams et al (2017), , Bouri et al (2016), Gil-Alana and Yaya (2014), Henriques and Sadorsky (2008), Huang et al (2017), Tule et al (2017), Tursol and Faisal (2017), Guo (2017), andSoyemi et al (2017) carry out the study nationally.…”
Section: Review Of Relevant Literaturementioning
confidence: 99%